Relations Entrance Test Interview with Learning Outcomes - Victor Simanjuntak (JETL (Journal of Education, Teaching and Learning), 2017)
The problem in this research is how the relationship between the results of tests Interview on learning outcomes. The approach used in this study was cross-sectional survey method. Population in this study were all students accepted at the Physical Education Program Health and Recreation (PJKR) Sports Sciences Department of the Faculty of Education (Guidance and Counseling) of Tanjungpura university for 2016/2017 amounted to 46 students. Sampling using saturation sampling technique is the determination of the sample by using the entire population of 46 people. Results showed that having interviews to higher learning outcomes are highly satisfactory 33 people (73%) and the results of interviews to low learning outcomes satisfy 1 (2%), while those with interviews to low learning outcomes that are very satisfying 1 (2%). For high-interview test results with the learning outcomes of praise amounting to 8 people (17%) and who had lower test interview with the learning outcomes of praise numbered 2 (4%).